Pengaruh Pemangkasan Cabang Lateral Terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) Varietas Etha 87 F1 - Tiffany Ramadhanie Suwandi; Elia Azizah; Yayu Agustini (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Pruning lateral branches is an effort to increase the growth and yield of cucumber plants. The research was conducted with the aim of obtaining pruning of lateral branches at the best age for the growth and yield of cucumber (Cucumis sativus L.) Etha 87 F1 variety. The experiment was carried out at the Agricultural Extension Center located in Sukamahi Village, Kec. Central Cikarang, Bekasi Regency, West Java. This experiment was carried out from June to August 2022. This research method used the Single Factor Randomized Block Design (RBD) experimental method with 7 treatments and 4 replicates to obtain 28 experimental units, the treatments consisted of: P0 (Control, without pruning), P1 (Pruning lateral branches 1-6 at 28 dap), P2 (Pruning lateral branches 1-6 at 35 dap), P3 (Pruning lateral branches 1-6 at 42 dap), P4 (Pruning lateral branches 7-12 age 28 dap), P5 (Pruning lateral branches of segments 7-12 aged 35 dap), and P6 (Pruning of lateral branches of segments 7-12 aged 42 dap). The results of this study indicated that pruning of lateral branches had a significant effect on the parameters of number of leaves, number of fruits, and fruit weight per plant. The P0 treatment gave the highest yield on the number of leaves per plant aged 35 hst (37.75 leaves) and 42 hst (38.75 leaves). The P4 treatment gave the number of fruits which was 5.17 fruits and the fruit weight per plant was 512.71 g/plant.